The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1468-4446.12651
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing covert surveillance: the subterranean world of policing

Abstract: In this article, I draw on data derived from an ethnographic field study of covert policing in the United Kingdom to demonstrate that the deployment of covert surveillance has become normalized, both in policing thought and operational practice. In a break with earlier patterns, the methods of covert surveillance are used extensively and are no longer regarded as a tactic of last resort. Covert policing is well anchored within organizational arrangements, empowered by a series of internal rationales mobilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…While police ethnographies have principally focused on uniformed officers operating at the base of the organisational structure, a number of studies have expanded their reach to examine the working values and practices of specialist units, including detectives (Young 1991, Bacon 2016, firearm units (Westmarland 2001) and covert operatives (Loftus et al 2016, Loftus 2019. Other work has focused on emerging modes of police, such as the non-warranted Police Community Support Officers (PCSOs) who are at the same time integral to, and marginalised from, the police organisation (O'Neill 2019).…”
Section: The Value Of Ethnographymentioning
confidence: 99%
See 1 more Smart Citation
“…While police ethnographies have principally focused on uniformed officers operating at the base of the organisational structure, a number of studies have expanded their reach to examine the working values and practices of specialist units, including detectives (Young 1991, Bacon 2016, firearm units (Westmarland 2001) and covert operatives (Loftus et al 2016, Loftus 2019. Other work has focused on emerging modes of police, such as the non-warranted Police Community Support Officers (PCSOs) who are at the same time integral to, and marginalised from, the police organisation (O'Neill 2019).…”
Section: The Value Of Ethnographymentioning
confidence: 99%
“…Police officers across most societies are bestowed with discretionary powers to stop, search, arrest and detain members of the public (Weber andBowling 2014, Skinns 2019). They are also permitted to undertake covert and intrusive surveillance against those people suspected of having committedor are in the course of committingcrimes (Marx 1988, Bacon 2016, Loftus 2019. Brodeur (2010) conceptualises these powers as 'extralegality in policing', in that police officers are authorised to use diverse means that are 'generally prohibited by statute or regulation to the rest of the population' (p. 130).…”
Section: Introductionmentioning
confidence: 99%
“…Acts of covert policing, such as directed surveillance, are an aspect of policing about which the general public has little knowledge. Furthermore, there is little empirical research on covert policing (Loftus and Goold 2012: 278;Loftus 2019). The goal of the present article is to contribute to this field.…”
Section: Introductionmentioning
confidence: 95%
“…Directed surveillance may be categorized as "covert and non-deceptive" surveillance (Marx 1988). It is not intrusive and is usually undertaken for a specific investigation or operation to obtain private information about a particular person (Loftus 2019) in order to aid an investigation or to prevent a crime (Bjerknes and Johansen 2009). When police conduct directed surveillance, they keep a person suspected of having committed or having intended to commit a criminal offence under surveillance without the individual's knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the authors demonstrated how exactly police officers manage to be invisible in order to infiltrate into suspect's daily routine. Loftus (2019) proved that today covert surveillance is a normal activity in Britain, which is legally regulated and having a lot of tools in its arsenal. As policing has become public business lately, covert measures are increasingly important.…”
Section: Literature Reviewmentioning
confidence: 99%